33.1.3.2 S-Alk-1-enylsulfoximides (Update 2018) - Kawecki,R. (Knowledge Updates 2018/4, 2019)
This chapter is an update to the earlier Science of Synthesis contribution describing methods for the preparation of alk-1-enylsulfoximides. This update focuses on methods published since 2004. It also covers the application of alk-1-enylsulfoximides in organic synthesis.
Keywords: sulfoximides; vinyl compounds; imination; Michael addition; furans